The Impact of Global Digital Trade Development on China’s Grain Import Trade Potential: An Empirical Analysis Based on a Time-Varying Stochastic Frontier Gravity Model - Dongpu Xu; Chunjie Qi; Guozhu Fang; Yumeng Gu (Agriculture)
It is of great significance to clarify the impact of the rapid development of digital trade on China’s grain imports in order to enhance its efficiency and guarantee food security. From an import perspective, this article adopts a stochastic frontier gravity model and a trade inefficiency model to analyze the influence of global digital trade development on the efficiency of China’s grain imports and further estimates the potential for trade expansion. The main findings include the following: (a) Divergence in digital trade capabilities persists across nations. As countries advance their digital trade ecosystems, China’s grain import efficiency demonstrates corresponding enhancements. (b) Compared with digital infrastructure construction and digital trade competition intensity, China’s food import trade efficiency increases as the level of digital technology innovation improves. (c) China achieves the highest trade efficiency in grain import among the ASEAN (Association of Southeast Asian Nations) and North American countries, while the greatest untapped potential lies in imports from South America. Accordingly, for different countries, it is necessary to adopt different strategies to enhance cooperation with the world’s major grain-trading countries in the areas of digital trade infrastructure construction and digital technology innovation, and to use digital trade to optimize China’s grain import trade chain and improve its efficiency.